Deterministic phase sequence approach for peak to average power ratio reduction in orthogonal frequency division multiplexing systems - Kazemian, Mohsen (2016)
Orthogonal Frequency Division Multiplexing (OFDM) is the current proposed approach in the several applicable wireless communication standards such as IEEE 802.15.3a, 802.11, and 802.16, and is utilized in the Digital Video Broadcasting (DVB) and European Digital Audio Broadcasting (DAB) systems. Stability against Inter Symbol Interference (ISI) and the high spectral efficiency are represented as the most important advantages of the OFDM system, however high Peak-to-Average Power Ratio (PAPR) is expressed as a major drawback of the mentioned system. When transmitted through a nonlinear power amplifier, this high PAPR signal creates spectral broadening and leads to low efficiency and low battery life; hence, the consumer electronics such as smart phones, tablet PCs and laptops in uplink communications usually are affected by these drawbacks.Several PAPR reduction techniques have been proposed in the literature such as coding, companding, Tone Reservation (TR), and clipping and filtering. The existing schemes are different from each other in terms of requirements, and the enforced restrictions to the systems. This thesis has studied based on two distortion-less methods called Conventional Selected Mapping (CSLM), and Conventional Partial Transmit Sequence (CPTS) which are two of the most efficient techniques in this research area.In this thesis, a unique idea is proposed and applied in the time domain and frequency domain, separately. Therefore, it needs to be applied based on the CPTS and the CSLM structures, respectively. This approach uses the non-random phase sequences, instead of the random ones as in CPTS and CSLM techniques. The proposed idea reduces the computational complexity, processing time and the side information matrix content, basically and ensures the results. The first proposed method, called Gray Code-based Phase sequence (GCP) is a new low complexity PAPR reduction scheme based on a Gray code structure and a similarity measurement block; included on two steps: firstly, selecting the phase sequences based on Gray codes and finally, evaluating the similarity between the input and the output of the Power Amplifier (PA), among the selected phase sequences in the previous step. By this approach, a significant reduction is provided in terms of the addition and the multiplication operation numbers together with the side information. The last stage is useful to reduce the Bit Error Rate (BER)performance degradation and out-of-band distortion. Simulations are based on IEEE 802.16e, Quadrature Phase Shift Keying (QPSK) modulation and performed with a power amplifier with memory effects. The proposed method provides a significant PAPR, BER performance degradation and out-of-band distortion reduction at almost the same total complexity compared with the CPTS and the Enhanced PTS (EPTS) techniques. More importantly, it is proved that at the same PAPR reduction value, this scheme provides a complexity reduction of at least 42.3% over that of the EPTS scheme, and leads to the out-of-band distortion reduction. Additionally, for the second method, the idea is applied on the CSLM scheme. Simplicity of the search algorithm, and the requirement for large numbers of Inverse Fast Fourier Transform (IFFT) blocks are the most important advantage and disadvantage of the CSLM scheme, respectively. The second proposed technique called Low complexity Radix-II SLM (LR-SLM) uses the special structure of an N-point radix-II IFFT in the CSLM method to overcome on the CSLM drawbacks and reduce the redundant calculations which leads to a reduction in terms of computational complexity, processing time and the side information matrix content, while achieving the same PAPR reduction, BER performance, and power spectral density (PSD) results as the CSLM scheme. The simulation results show that the computational complexity is reduced by at least 46.8% compared with the CSLM scheme with approximately the same PAPR performance.In order to evaluate the effect of these methods in the actual system, the PSD of the output signal when applying the predistortion block and the PA, is provided. The results show that the GCP method improves the PSD of the signal at least 4dB, compared with the CPTS method. Furthermore, it is shown that the PSD of the LR-SLM method does not differ with that of the CSLM.